The 'Accursed' Artist in the Literature and the Art of Symbolism - Tsoumas, Johannis (2012)
This article aims at revising a particularly interesting area of European history of Art and Literature which rests within the turbulent era of the late 19th century: the Symbolist Movement. Through the reading of the principles and axioms of its both literary and aesthetic characteristics, we will attempt an in-depth understanding of its interrelationship with the concepts of decline, derangement and error, the metaphysical element, the collapse and death, of human passions. But how these, for many people charming, while for others, gruesome details are encapsulated in life and / or the work of the main advocates of Symbolism? Our interest will focus on their own bitter or hedonic truth from within which some of the greatest masterpieces of literature and art were generated, while the creators themselves were classified in the list of the damned genius.